Implementation of IoT-based STEM-Contextual learning with the MQTT protocol on the digital literacy skills of pre-service science teacher - Didik Setyawarno; Dadan Rosana; Ibrohim; Erti Hamimi; Ade Gafar Abdulloh (LUMAT)
The Internet of Things (IoT) with the Message Queue Telemetry Transport (MQTT) protocol in learning processes is one of the learning innovations in the digital era which has a significant role in students' digital literacy skills. Moreover, the STEM-contextual approach is in line with the demands of 21st-century learning. The authors attempt to integrate IoT with MQTT protocol in STEM-Contextual learning. This study aims to determine the results of the implementation of STEM-Contextual learning based on the IoT with the MQTT protocol on the digital literacy skills of pre-service science teachers. The research used a one-shot case study design. The research sample was pre-service science teacher students from Universitas Negeri Yogyakarta (UNY), totalling 43, and from Universitas Negeri Malang (UM), totalling 66, determined by convenience sampling technique. The research instruments used were a questionnaire sheet on digital literacy skills and an observation sheet on STEM-Contextual learning implementation. The quality of the instrument was analyzed using the content validity ratio, Fleiss Kappa, confirmatory factor analysis, and Rasch model. Data analysis of digital literacy skills used descriptive statistics, the conversion of quantitative to qualitative scales, and inferential statistics. The finding shows a significant positive effect of implementing IoT-based STEM-contextual learning with the MQTT protocol on the digital literacy skills of pre-service science teachers at UNY and UM. The total score of pre-science teachers of UNY is 70.98 in the High Performers category, while the pre-science teachers of UM are 67.52 in the Above Average Performers category.